THE EFFECTIVENESS METHODS FOR ACTIVATING STUDENTS' INDEPENDENT WORK IN FOREIGN LANGUAGE LESSONS (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article discusses effective methods for enhancing students’ independent work in foreign language lessons.